2005
DOI: 10.1007/bf03016068
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanesthesia and Intensive Care Limited ability of SOFA and MOD scores to discriminate outcome: a prospective evaluation in 1,436 patients

Abstract: P Pu ur rp po os se e: : The multiple organ dysfunction (MOD) score and sequential organ failure assessment (SOFA) score are measures of organ dysfunction and have been validated based on the association of these scores with mortality. We sought to compare the performance of the SOFA and MOD scores in a large cohort of consecutive multisystem intensive care unit (ICU) patients.M Me et th ho od ds s: : Prospective automated daily measurements of MOD and SOFA scores were performed in 1,436 patients admitted to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
57
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 29 publications
(21 reference statements)
6
57
0
2
Order By: Relevance
“…[11][12][13][14][15] In the present study, mortality was 34%, which is comparable to that reported in previous studies from India (40.3%) and Indonesia (39.8%). 16 It is higher compared with those reported in Germany (9%), Australia (16%), and Saudi Arabia (31.6%). [17][18][19] The high mortality can be attributed to shortage of ICU beds in our centre (ICU bed: hospital bed ratio is 0.006).…”
Section: Discussionmentioning
confidence: 64%
“…[11][12][13][14][15] In the present study, mortality was 34%, which is comparable to that reported in previous studies from India (40.3%) and Indonesia (39.8%). 16 It is higher compared with those reported in Germany (9%), Australia (16%), and Saudi Arabia (31.6%). [17][18][19] The high mortality can be attributed to shortage of ICU beds in our centre (ICU bed: hospital bed ratio is 0.006).…”
Section: Discussionmentioning
confidence: 64%
“…The SOFA was developed based on the degree of organ dysfunction. However, some publications have questioned the reliability of these scoring systems [12][13]. As expected, both the APACHE and SOFA scores were higher in patients with a poor outcome than in patients who survived, but only the SOFA score proved to be a predictor of death at time zero.…”
Section: Discussionmentioning
confidence: 72%
“…However, some publications have questioned the insufficient reliability of these scoring systems [12][13]. In fact, many publications focused their attention on using the plasma levels of certain factors, such as protein C (PC), procalcitonin, TNF-, and plasminogen activator inhibitor-1 (PAI-1), as prognostic markers [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the journal, 10 Zygun and his colleagues in Calgary have taken advantage of the tremendous data management capacity of an electronic patient information system to compare two commonly used tools for measuring organ dysfunctionthe Sequential Organ Failure Assessment (SOFA) score developed through a consensus process by the European Society of Intensive Care Medicine in 1994, 11 and the Multiple Organ Dysfunction (MOD) score, a Canadian scale developed in the late 1980's and early 1990's, using an iterative process that sought to maximize construct, content, and criterion validity. 12,13 They conclude that there is little difference between the two scales in their ability to discriminate outcome, and that neither performs particularly well when evaluated on the basis of their discriminatory ability and calibration.…”
mentioning
confidence: 99%
“…Dans le présent numéro du journal, 10 Zygun et ses collègues de Calgary ont tiré avantage de la formidable capacité de gestion des données d'un réseau d'information électronique sur les patients pour comparer deux outils de mesure de la dysfonction organique couramment utilisés -le Sequential Organ Failure Assessment (SOFA) score développé à partir d'un consensus par la European Society of Intensive Care Medicine en 1994, 11 et le Multiple Organ Dysfunction (MOD) score, échelle canadienne élaborée à la fin des années 1980 et au début des années 1990, en utilisant un processus itératif qui tente de maximiser la validité du construit, du contenu et des critères. 12,13 Il existe, selon eux, une petite différence entre les deux échelles quant à la capacité de caractériser les résultats, mais aucune ne fonctionne particulièrement bien quand on les évalue sur leur capacité discriminante et leur calibrage.…”
unclassified